Implementation of the Lontar Wreti Sasana Teachings for Pemangku - Sri Diantari, Putu Ayu Wulan; Mastini, Gusti Nyoman (Jayapangus Press, 2023)
The existence of Hinduism always upholds and respects local traditions, local culture and customs adopted by the village or local area. Traditions that are sourced from literature or lontar made by spiritualists or poets. Bali, which is rich in Hindu literature, is local and rich in sources of Hindu religious teachings from traditional texts, both in the form of prasasti, lontar, tutur, babad, pupuh and other forms. One of the lontars that are still used today, in particular, is the Lontar Wreti Sasana which is a lontar which describes how the rules of a pemangku in carrying out their obligations in society. Next, the background behind discussing further about the teachings of Lontar Wreti Sasana is wanting to introduce Lontar Wreti Sasana to the younger generation and prospective pemangku so that they are able to know that Lontar Wreti Sasana is a lontar which contains rules for being a pemangku and needs to be preserved so that it does not heredity with time. Data collection methods used are literature study, observation, interviews and documentation. The data collected were analyzed using descriptive qualitative analysis method with data reduction steps, data presentation and drawing conclusions. The results showed, 1) Lontar Wreti Sasana contains the teachings of panca yama brata and panca niyama brata. 2) Hindu religious education values ​​contained in Lontar Wreti Sasana, namely religious education values, ethical education values ​​and social values ​​(3) implementation of teachings in Lontar Wreti Sasana for pemangku in Pelaga Village that most pemangku have implemented the contents of Lontar Wreti Sasana ie not eating any food (aharalaghawa), only taking one wife after the study period (krisna brahmacari), not taking a wife who should not be his wife (agamyagamana), never telling lies and harsh words and words that hurt others (satya), has never dealt with the law (awyawahara), then is not negligent in carrying out duties (apramada). So the teachings in Lontar Wreti Sasana are gym texts for someone wreti, namely people who carry out wrata or brata, namely the promise and realization of life based on religious teachings.